Contactless Triboelectric Sensing for Real‐Time 3D Motion Recognition in Human‐Computer Interaction - Qinghao Xu; Junhao Gong; Jiayi Chen; Yimeng Zhang; Hongfa Zhao; Jiaqi Yin; Runze Zhao; Chuqiao Lyu; Wenbo Ding; Changsheng Wu (Advanced Electronic Materials, 2025)
Abstract In the rapidly advancing fields of artificial intelligence and the Internet of Things, there is a growing need for human‐computer interaction (HCI) solutions that are not only intuitive but also efficient and easy to use. Triboelectric nanogenerators present a promising approach to developing wireless human‐machine interfaces, offering advantages such as simple operating principles and flexible, adaptable designs. This study introduces an HCI system that leverages a contactless triboelectric detector (CTD) to classify complex motion patterns in 3D space. The CTD system consists of a contactless sensing panel, a silicone rubber finger sleeve, a signal acquisition circuit, and a mobile terminal, which together enable the seamless acquisition and classification of weak wireless signals. One of the key benefits of the system is its lack of active energy consumption, making it highly energy‐efficient. Additionally, its simple structure and ease of deployment make it an attractive option for various applications. Experimental results illustrate that the proposed system has significant potential for interactive perception in industrial environments. With a motion recognition accuracy of 99.33%—including for intricate motions such as spiral curves—this system demonstrates its potential as a next‐generation solution for wireless HCI systems.